DETERMINASI STABILITAS KEUANGAN BANK SYARIAH DI INDONESIA DAN MALAYSIA - Gema Sakha Tikta (2023)
This research is a quantitative study that aims to determine the effect of liquidity risk, credit risk, capital adequacy and bank size on the financial stability of Islamic banks. Modified the regression model based on Sharia Enterprise Theory. Using panel data regression on 14 BUS (Sharia Commercial Banks) in Indonesia and 14 Islamic Banks in Malaysia with the year of observation for the 2019-2021 period. The results of this study found that financial stability is entirely God's will and mathematically, results of this study found that only liquidity risk and capital adequacy variables had an effect on the financial stability of Islamic banks. However, credit risk and bank size variables have no effect on the financial stability of Islamic banks. The results of this study are expected to provide a reference for regulators to consider components that can affect the financial stability of Islamic banks in order to consistent in maintaining good financial stability.